Analysis of the influence of product quality and service quality on customers’ repurchase intention at Restaurant X mediated by customer satisfaction - Regina Widjaja; Theresia Gunawan (Universitas Nusa Cendana, 2026)
This study considers the effects of product quality as well as service quality on repurchase intention, with a mediating variable which is customer satisfaction, within the context of Restaurant X, a steakhouse operating in Indonesia’s competitive food and beverage sector. A quantitative methodology was adopted, drawing on data from 103 valid respondents obtained through an online survey. Data analysis utilized Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings demonstrate that product quality has a direct effect that is positive and statistically significant on repurchase intention, while customer satisfaction shows a positive effect on customers' intentions to return and make additional purchases. Additionally, customer satisfaction significantly mediates the relationships between product quality with repurchase intention, as well as between service quality with repurchase intention. These findings indicate that high-quality products and services primarily encourage repeat purchases by enhancing customer satisfaction. The results highlight the strategic importance of maintaining consistent product excellence along with superior service quality to foster customer loyalty in the restaurant industry. This study gives a contribution to the hospitality and consumer behaviour literature by clarifying customer satisfaction’s mediating role in repurchase intention and provides practical recommendations for restaurant managers seeking to make improvements on customer retention and lasting business performance. Keywords: Product Quality; Service Quality; Customer Satisfaction; Repurchase Intention; PLS-SEM